Thin Bioactive Zn Substituted Hydroxyapatite Coating Deposited on Ultrafine-Grained Titanium Substrate: Structure Analysis - Prosolov, Konstantin A.; Belyavskaya, Olga A.; Muehle, Uwe; Sharkeev, Yurii P. (Frontiers in Materials, 2018)
Nanocrystalline Zn substituted hydroxyapatite coatings were deposited by radiofrequency magnetron sputtering on the surface of ultrafine-grained titanium substrates. Cross section transmission electron microscopy provided information about the morphology and texture of the thin film while in-column energy dispersive X-ray analysis confirmed the presence of Zn in the coating. The Zn substituted hydroxyapatite coating was formed by an equiaxed polycrystalline grain structure. Effect of substrate crystallinity on the structure of deposited coating is discussed. An amorphous TiO2 sublayer of 8 nm thickness was detected in the interface between the polycrystalline coating and the Ti substrate. Its appearance in the amorphous state is attributed to prior to deposition etching of the substrate and subsequent condensation of oxygen-containing species sputtered from the target. This layer contributes to the high coating-to-substrate adhesion. The major P-O vibrational modes of high intensity were detected by Raman spectroscopy. The Zn substituted hydroxyapatite could be a material of choice when antibacterial osteoconductive coating with a possibility of withstanding mechanical stress during implantation and service is needed.